Disruption, not displacement: Environmental variability and temporary migration in Bangladesh. (September 2017) - Call, Maia A.; Gray, Clark; Yunus, Mohammad; Emch, Michael
Highlights: Riverine flooding does not have a long-term impact on temporary migration. Optimal precipitation and above average temperatures have sustained positive effects on temporary migration. Households in Matlab, Bangladesh draw on a range of strategies to cope with environmental variability. Abstract: Mass migration is one of the most concerning potential outcomes of global climate change. Recent research into environmentally induced migration suggests that relationship is much more complicated than originally posited by the 'environmental refugee' hypothesis. Climate change is likely to increase migration in some cases and reduce it in others, and these movements will more often be temporary and short term than permanent and long term. However, few large-sample studies have examined the evolution of temporary migration under changing environmental conditions. To address this gap, we measure the extent to which temperature, precipitation, and flooding can predict temporary migration in Matlab, Bangladesh. Our analysis incorporates high-frequency demographic surveillance data, a discrete time event history approach, and a range of sociodemographic and contextual controls. This approach reveals that temporary migration declines immediately after flooding but quickly returns to normal. In contrast, high temperatures have sustained positive effects on temporary migration that persist over one to two year periods, while migrations decrease during extended periods of extreme precipitation. Building on previous studies of long-term migration, these results challenge the common assumption that flooding, precipitation extremes, and high temperatures will consistently increase temporary migration. Instead, our results are consistent with a livelihoods interpretation in which long-standing household livelihood strategies (both temporary migration and agriculture) are disrupted by environmental variability.